2011
DOI: 10.1111/j.1556-4029.2011.01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simple GC–MS Method for Determination of Psychotropic Phenylalkylamine Derivatives in Nails Using Micro‐Pulverized Extraction*

Abstract: A rapid and simple gas chromatography-mass spectrometry (GC-MS) method was developed and validated for the simultaneous detection and quantification of five psychotropic phenylalkylamines (amphetamine, methamphetamine, 3,4-methylenedioxyamphetamine, 3,4-methylenedioxymethamphetamine, and norketamine) in toenails. After external decontamination, nail clippings were mechanically pulverized with a bead mill and then incubated in methanol under ultrasonication at 50°C for 1 h. The resulting solutions were evaporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…Fingernails of seven drug abusers were analyzed for mAMP (six positive cases; 0.23-2.09 ng/mg), AMP (four positive cases; \0.063 ng/mg), MDA (one positive case; \0.143 ng/mg), and MDMA (one positive case; 0.46 ng/mg) [24]. In toenails of four drug abusers, mAMP and AMP were both detected in one case (concentrations not provided) [25]. A larger study in 97 female AMP and/or opiate drug users, who were currently under treatment, reported the duration of detectability and deposition characteristics of mAMP and AMP in fingernails [16]; 62 subjects were found positive for mAMP and/or AMP, with concentrations ranging from 0.46 to 61.5 ng/mg and from\0.2 to 5.42 ng/mg, respectively.…”
Section: Amphetamine Detection and Quantification In Nailsmentioning
confidence: 98%
See 3 more Smart Citations
“…Fingernails of seven drug abusers were analyzed for mAMP (six positive cases; 0.23-2.09 ng/mg), AMP (four positive cases; \0.063 ng/mg), MDA (one positive case; \0.143 ng/mg), and MDMA (one positive case; 0.46 ng/mg) [24]. In toenails of four drug abusers, mAMP and AMP were both detected in one case (concentrations not provided) [25]. A larger study in 97 female AMP and/or opiate drug users, who were currently under treatment, reported the duration of detectability and deposition characteristics of mAMP and AMP in fingernails [16]; 62 subjects were found positive for mAMP and/or AMP, with concentrations ranging from 0.46 to 61.5 ng/mg and from\0.2 to 5.42 ng/mg, respectively.…”
Section: Amphetamine Detection and Quantification In Nailsmentioning
confidence: 98%
“…Washing has usually been followed by alkaline extraction and further clean-up with liquid-liquid extraction (LLE) [8,16,[22][23][24]. In recent years, a rapid and easy sample preparation procedure was proposed in which decontamination was immediately followed by mechanical pulverization of the nail, methanol extraction, and purification by high speed centrifugation [25]. Thereby, alkaline extraction, which can result in the loss of amphetamines by evaporation, was avoided.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, following such digestion, some components of interest may be decomposed. Thus, alternative methods of extraction are occasionally implemented; for example, ultrasound-assisted extraction with methanol (after micropulverization of the specimen) [50,51]. To remove matrix interferences (especially after digestion), subsequent clean-up by solid-phase extraction (SPE) is necessary [48].…”
Section: (A) Hair and Nailmentioning
confidence: 99%